2018
DOI: 10.3389/fphar.2018.00819
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Activation Provides Atheroprotection in Diabetic Mice Through Concerted Upregulation of Antioxidant, Anti-inflammatory, and Autophagy Mechanisms

Abstract: Interactive relationships between metabolism, inflammation, oxidative stress, and autophagy in the vascular system play a key role in the pathogenesis of diabetic cardiovascular disease. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a stress-sensitive guarantor of cellular homeostasis, which cytoprotective contributions extend beyond the antioxidant defense. We investigated the beneficial effects and underlying mechanisms of the Nrf2 inducer tert-butyl hydroquinone (tBHQ) on diabetes-driven atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 65 publications
(100 reference statements)
4
53
0
Order By: Relevance
“…Nuclear factor-2 erythroid related factor (Nrf2)-keep 1 pathway has been also shown to play a major role in the progression of DKD [87]. Pharmacological activation of Nrf2 decreases cytokine production, M1 macrophage accumulation, and the formation of an atherosclerotic plaque lipid core in the experimental model of streptozotocin-induced diabetic mice on an apolipoprotein E-deficient background [88]. In addition, its activation improves the pathological changes in the glomerulus of streptozotocin-induced diabetic mice through a reduction in oxidative stress, TGF-β expression, and extracellular matrix proteins [89].…”
Section: Challenges and Opportunities In Developing New Therapies Formentioning
confidence: 99%
“…Nuclear factor-2 erythroid related factor (Nrf2)-keep 1 pathway has been also shown to play a major role in the progression of DKD [87]. Pharmacological activation of Nrf2 decreases cytokine production, M1 macrophage accumulation, and the formation of an atherosclerotic plaque lipid core in the experimental model of streptozotocin-induced diabetic mice on an apolipoprotein E-deficient background [88]. In addition, its activation improves the pathological changes in the glomerulus of streptozotocin-induced diabetic mice through a reduction in oxidative stress, TGF-β expression, and extracellular matrix proteins [89].…”
Section: Challenges and Opportunities In Developing New Therapies Formentioning
confidence: 99%
“…Moreover, as shown on the present experimental model, the ROS accumulation (in particular in DTF group) coupled with the impair of cellular thiols, namely MTs and glutathione, disturbed bone healing after fracture. Obviously, manipulations with Nrf2 should optimize efficiency of bone remodeling via regulation of antioxidants/prooxidants balance, alteration of oxidative stress genes and affection of mitochondrial ROS production [40], but further studies are needed.…”
Section: Resultsmentioning
confidence: 99%
“…The present study sought to use NPs to target atherosclerotic plaque through passive targeting means in [15][16][17][18][19] week old ApoE -/and LDLr -/mice fed with an HFD. Herein we generated two types of NPs: 1.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did show that our NP formulation exhibited a delayed release of CDDO-Me to active Nrf2 in vitro. Moreover, in the literature it has previously been shown that activation of Nrf2 in LDLr -/with tBHQ can have atheroprotective effects based on the alleviation of oxidative stress and limitation of inflammation 19 . It is known that Nrf2 activation inhibits VSMC migration 37 .…”
Section: Cddo-me-npsmentioning
confidence: 99%